The Causes of Ukrainian Famine Mortality, 1932–33 - Markevich, Andrei; Naumenko, Natalya; Qian, Nancy (Review of Economic Studies, 2025)
Abstract We construct a novel panel dataset for interwar Soviet Union to study the causes of Ukrainian famine mortality (Holodomor) during 1932–3 and document several facts: (1) Ukraine produced enough food in 1932 to avoid famine in Ukraine; (2) 1933 mortality in the Soviet Union was increasing in the pre-famine ethnic Ukrainian population share and (3) was unrelated to food productivity across regions; (4) this pattern exists even outside of Ukraine; (5) migration restrictions exacerbated mortality; (6) actual and planned grain procurement were increasing and actual and planned grain retention (production minus procurement) were decreasing in the ethnic Ukrainian population share across regions. The results imply that anti-Ukrainian bias in Soviet policy contributed to high Ukrainian famine mortality, and that this bias systematically targeted ethnic Ukrainians across the Soviet Union.